CIRCADIAN RHYTHM AND SLEEP DISTURBANCES IN NEURODEGENERATION: BIOMARKERS, DISEASE PROGRESSION, AND INTERVENTIONS - Jakub Przerwa (International Journal of Innovative Technologies in Social Science, 2025)
In neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and frontotemporal dementia, sleep disturbances and dysregulation of the sleep–wake cycle constitute a significant clinical problem. These disturbances are not only a manifestation of disease progression but may also contribute to its exacerbation through complex effects on physiological processes. This article analyzes the relationship between neurodegenerative disease progression and sleep disorders, considering molecular, neurophysiological, and digital biomarkers as well as the effectiveness of chronobiological interventions. The review indicates that circadian rhythm disturbances occur in all aforementioned disease entities and are strongly associated with motor and neuropsychological symptoms. Interventions targeting insomnia-such as lifestyle modification, melatonin supplementation, and light therapy-demonstrate moderate efficacy in improving cognitive function. Biomarkers used to assess their effectiveness include changes in EEG, cortisol and melatonin profiles, and the expression of clock genes (PER2, BMAL1).